Influence of Kinesitherapy on Functional Independence in Patients with Supratentorial Unilateral Stroke in Chronic Period - Danche Vasileva; Daniela Lubenova; Darina Zaharieva; Kristin Grigorova-Petrova; Milena Nikolova; Tzvetalina Bizeva (European Scientific Journal, ESJ, 2017)
Aim: The aim of the study is to evaluate the effect of the specialized kinesitherapeutic (KT) methodology (SKTM) on functional independence in patients with supratentorial unilateral stroke in the chronic period (SUSChP). Material and Methods: The study was conducted with 67 patients with SUSChP (56 patients included in the experimental group - 32 men and 24 women, with duration of the disease 7.8 ± 2.0 months, and 11 patients in the control group - 9 men and 2 women, with duration of the disease 7.3 ± 1.5 months). To evaluate the changes in functional independence, test for Functional Independence Measure (FIM) was used. Patients in the experimental group were treated with a specialized 10-day KT, which later continued to be performed as an adapted exercise program at home for a period of one month. Control patients perform a regular 10-day KT. This was done using SKTM principles of modern neurorehabilitation and motor learning as opposed to usual kinesitherapy. Results: After applying SKTM, the highest trend towards the improvement of functional independence was established after the 1st month with a level of significance during treatment p<0.001. Conclusion: In conclusion, the enclosed SKTM in the experimental group continued later as an adapted exercise program at home. It significantly improves the functional independence in patients with supratentorial unilateral stroke in the chronic period (SUSChP) compared  with the usual kinesitherapeutic methodology applied in the control group.